2020
DOI: 10.1186/s12933-020-01073-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saroglitazar 2 mg and 4 mg on glycemic control, lipid profile and cardiovascular disease risk in patients with type 2 diabetes mellitus: a 56-week, randomized, double blind, phase 3 study (PRESS XII study)

Abstract: Background: The potential for PPAR agonists to positively affect risk of cardiovascular disease in patients with type 2 diabetes (T2DM) is of persistent attention. The PRESS XII study primarily aimed to evaluate the efficacy and safety of saroglitazar (2 mg and 4 mg) as compared to pioglitazone 30 mg on glycemic control in patients with type 2 diabetes mellitus. Methods: In this randomized double-blind study, patients with T2DM [glycosylated hemoglobin (HbA1c) ≥ 7.5%] were enrolled from 39 sites in India. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 51 publications
(60 reference statements)
3
33
0
Order By: Relevance
“…In a post hoc analysis, elafibranor resolved NASH without fibrosis worsening and did not cause cardiac events [398]. Saroglitazar showed a potential to lower the cardiovascular risk in T2DM patients [418]. Pemafibrate is currently being tested for its effect on reducing cardiovascular events in diabetic patients with high TG levels in the PROMINENT study (NCT03071692) [390].…”
Section: Resultsmentioning
confidence: 99%
“…In a post hoc analysis, elafibranor resolved NASH without fibrosis worsening and did not cause cardiac events [398]. Saroglitazar showed a potential to lower the cardiovascular risk in T2DM patients [418]. Pemafibrate is currently being tested for its effect on reducing cardiovascular events in diabetic patients with high TG levels in the PROMINENT study (NCT03071692) [390].…”
Section: Resultsmentioning
confidence: 99%
“…It also indicated that no significant changes can be observed in blood hemo-globin A1c (HbA1c), total/low density lipoprotein (LDL)/high density lipoprotein (HDL) cholesterol, and apolipoprotein-B. 32) With saroglitazar, there were no serious safety concerns, such as edema, carcinogenic potential, and cardiovascular side effects, except for a significant increase in serum creatinine. 32) Another recent study noted that saroglitazar treatment effectively improved glycemic control and lipid parameters over a 56-week period in patients with T2DM who received background metformin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials with tesaglitazar, aleglitazar and muraglitazar have been terminated due to side effects such as oedema and possible renal complications. Saroglitazar has been shown to significantly decrease both glucose and lipids [27] and has been approved recently in India for the treatment of NASH after the Phase III EVIDENCES-II trial showed histological improvement of NASH using liver biopsy after 52 weeks of treatment [28,29]; However, these data were only presented at conferences and there is only evidence of reduction in liver stiffness measured using FibroScan [29]. The Phase II EVIDENCES-IV trial is currently investigating the effect of saroglitazar in US individuals with NAFLD/ NASH.…”
Section: Nuclear Hormone Receptor Agonistsmentioning
confidence: 99%